SNP Analysis of Caries and Initial Caries in Finnish Adolescents. (23rd April 2018) - Raivisto, Teija; Heikkinen, AnnaMaria; Kovanen, Leena; Ruokonen, Hellevi; Kettunen, Kaisa; Tervahartiala, Taina; Haukka, Jari; Sorsa, Timo
Abstract : Background . Dental caries is the most common infection in the world and is influenced by genetic and environmental factors. Environmental factors are largely known, but the role of genetic factors is quite unknown. The aim was to investigate the genetic background of caries in Finnish adolescents. Materials and Methods . This study was carried out at the Kotka Health Center in Eastern Finland. 94 participants aged 15–17 years gave approval for the saliva and DNA analyses. However, one was excluded in DNA analysis; thus, the overall number of participants in analysis was 93. Caries status was recorded clinically and from bite-wing X-rays to all 94 participants. Genomic DNA was extracted by genomic QIAamp® DNA Blood Mini Kit and genotyped for polymorphisms. The results were analyzed using additive and logistic regression models. Results . No significant associations between caries and the genes studied were found. However, SNPs in DDX39B and MPO showed association tendencies but were not statistically significant after false discovery rate (FDR) analysis. SNPs in VDR, LTA, and MMP3 were not statistically significant with initial caries lesions after FDR analysis. Conclusion . The present study could not demonstrate statistically significant associations between caries and the genes studied. Further studies with larger populations are needed.